Evaluation of a universal flow-through model for predicting and designing phosphorus removal structures. (May 2016) - Penn, Chad; Bowen, James; McGrath, Joshua; Nairn, Robert; Fox, Garey; Brown, Glenn; Wilson, Stuart; Gill, Clinton
Abstract: Phosphorus (P) removal structures have been shown to decrease dissolved P loss from agricultural and urban areas which may reduce the threat of eutrophication. In order to design or quantify performance of these structures, the relationship between discrete and cumulative removal with cumulative P loading must be determined, either by individual flow-through experiments or model prediction. A model was previously developed for predicting P removal with P sorption materials (PSMs) under flow-through conditions, as a function of inflow P concentration, retention time (RT), and PSM characteristics. The objective of this study was to compare model results to measured P removal data from several PSM under a range of conditions (P concentrations and RT) and scales ranging from laboratory to field. Materials tested included acid mine drainage residuals (AMDRs), treated and non-treated electric arc furnace (EAF) steel slag at different size fractions, and flue gas desulfurization (FGD) gypsum. Equations for P removal curves and cumulative P removed were not significantly different between predicted and actual values for any of the 23 scenarios examined. However, the model did tend to slightly over-predict cumulative P removal for calcium-based PSMs. The ability of the model to predict P removal for various materials, RTs, and P concentrations in both controlled settings and field structures validate its use in design and quantification of these structures. This ability to predict P removal without constant monitoring is vital to widespread adoption of P removal structures, especially for meeting discharge regulations and nutrient trading programs. Graphical abstract: Highlights: Evaluated flow-through model for predicting phosphorus (P) removal by materials. Model considered material characteristics, retention time, and P concentration. P removal predictions were successful from lab to field-scale P removal structures. Model can be used to design P removal structures or predict performance. Model incorporated into design software, "Phrog".